Desain Prototipe Sistem Keamanan Rumah Berbasis Internet Of Things dengan Integrasi Sensor Pintar - Abidin, Zainal; Nugraha, Rizky Ananda; Santoso, Eko Wahyu (ELECTRA : Electrical Engineering Articles, 2026)
The rise in crime, especially theft, in residential areas demands a smarter and more efficient security system. This research designs a prototype Internet of Things (IoT)-based home security system with the integration of various smart sensors that can be controlled and monitored remotely. The ESP32-Wrover-CAM microcontroller is used as the control center, supported by an RC522 RFID sensor, an AM312 PIR sensor, a reed switch, an OV2640 camera, a buzzer, and a door lock solenoid. Test results show the system is capable of detecting motion, unlocking the door using an RFID card, and sending photos and real-time notifications via Telegram with an average response time of 0.86 seconds at an internet speed of 8.32 Mbps. The system successfully improves home security efficiently and can be controlled both ways (manually and online).